Seasonal changes in semen quality and correlation with plasma hormone profiles in Karan Fries bulls. Issue 6 (1st November 2016) - Mallick, Smrutirekha; Aggarwal, Anjali; Prakash, B. S.
Abstract: The aim of the study was to assess the influence of summer and winter seasons on semen quality and plasma hormone concentrations in cross-bred bulls. Semen was collected by an artificial vagina from eight bulls and microscopically evaluated for quality parameters. Semen volume was higher in summer season ( p  < 0.05) than winter season, whereas nonsignificant variation ( p  > 0.05) was observed in mass motility, individual motility, sperm viability, sperm concentration and percentage of membrane-intact and acrosome-intact spermatozoa. Plasma prolactin and testosterone concentration were significantly ( p  < 0.01) higher in summer season than winter season. Plasma testosterone levels were positively correlated with semen volume and negatively correlated with individual motility ( p  < 0.05). Prolactin showed a significant positive correlation with semen volume. A well-defined seasonal pattern in semen characteristics was not observed and few correlations existed between plasma hormone levels and semen characteristics in Karan Fries bulls.